PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Winarti, Dewi; Imron, Moch (Universitas Ahmad Dahlan, 2013)
Corporate social responsibility is mechanism for a company voluntarily integrated concern for the environment and society. Disclosure of corporate social responsibility has a tendency to influence influential to enhance shareholder value. With the increased value of the company, then investors will be attracted to invest on companies that care a bout the social environment. The growing public awareness of the social environment requires employers not ignore the interests of the social environment around the company. Good corporate governance is a major problem in the management of the administration of the company, the management company that leads the company to more accountable and transparent in every policy of and the result in gactions. Study aims to determine the effect of corporate social responsibility and corporate governance on firm valueto firm size as a moderating variable. There search sample in this study is a manufacturing company listed on the Stock Exchange in the year 2009 – 2012 by using purposive sampling. There are 56 companies that meet the criteria of the study sample. The analysis techniques in this study using multiple linear regression analysis and linear regression analysis testing the interaction (moderated regression analysis / MRA). The results of this study indicate that the disclosure and corporate governance and corporate social responsibility have no effect on firm value. While the size of the company is not able to moderate the influence of corporate social responsibilty disclosure and corporate governance on firm value. So the conclusion all the hypothesis in this study was rejected